The Authority of State Agencies in Illegal Fishing Investigations: Harmonizing Enforcement and Addressing Jurisdictional Overlaps - I Gusti Bagus Yoga Sastera; Putu Gede Arya Sumerta Yasa; I Nyoman Bagiastra (APPTHI, 2023)
Abstract. The location of Indonesia which is between two continents and two oceans makes Indonesia vulnerable to criminal acts in the field of fisheries. This study aims to investigate the authority of state agencies in the investigation stage of illegal fishing crimes in Indonesian territorial waters. Research approach used in this study is through a normative juridical approach or the study of literature and documents aimed at written regulations or other legal materials related to the guarantee of legal certainty for the investigation of illegal fishing crimes in Indonesia. The results showed that for the handling of these criminal acts, legal politics in the formulation of Law No. 31 of 2004 concerning Fisheries stipulates that investigations into fisheries crimes are carried out by Civil Servants of Fisheries Investigators, Investigating Officers of the Indonesian Navy, and Indonesian National Police. The law does not provide strict limitations on the investigative powers of these three agencies, even with Law No. 45 of 2009 as an amendment to Law No. 31 of 2004 also does not clearly regulate the limits of the investigative authority of the three agencies. Therefore, in its implementation there may be overlap of authority. Therefore, it is necessary to harmonize law enforcement in the investigation stage. Keywords: Criminal Investigation, Criminal Act, Law Enforcement, Illegal Fishing, Jurisdictional Overlaps Abstrak. Letak Indonesia yang berada di antara dua benua dan dua samudera menjadikan Indonesia rentan terhadap tindak pidana di bidang perikanan. Penelitian ini bertujuan untuk mengetahui kewenangan lembaga negara dalam tahap penyidikan tindak pidana illegal fishing di wilayah perairan Indonesia. Pendekatan penelitian yang digunakan dalam penelitian ini adalah melalui pendekatan yuridis normatif atau studi literatur dan dokumen yang ditujukan pada peraturan tertulis atau bahan hukum lainnya terkait dengan jaminan kepastian hukum dalam penyidikan tindak pidana illegal fishing di Indonesia. Hasil penelitian menunjukkan bahwa untuk penanganan tindak pidana tersebut, politik hukum dalam rumusan Undang-Undang Nomor 31 Tahun 2004 tentang Perikanan mengatur bahwa penyidikan tindak pidana perikanan dilakukan oleh Penyidik Pegawai Negeri Sipil, Penyidik TNI Angkatan Laut, dan Penyidik Perikanan. Kepolisian Negara Republik Indonesia. Undang-undang tidak memberikan batasan tegas mengenai kewenangan penyidikan ketiga lembaga tersebut, bahkan dengan adanya Undang-Undang Nomor 45 Tahun 2009 sebagai perubahan atas UU Nomor 31 Tahun 2004 juga tidak mengatur secara jelas batasan kewenangan penyidikan ketiga lembaga tersebut. Oleh karena itu, dalam pelaksanaannya mungkin terjadi tumpang tindih kewenangan. Oleh karena itu, perlu adanya harmonisasi penegakan hukum pada tahap penyidikan. Kata kunci: Penyidikan Pidana, Tindak Pidana, Penegakan Hukum, Penangkapan Ikan Ilegal, Tumpang Tindih Yurisdiksi